Patients' perspectives on how to decrease the burden of treatment: a qualitative study of HIV care in sub-Saharan Africa. Issue 4 (29th April 2018) - Tran, Viet-Thi; Messou, Eugene; Mama Djima, Mariam; Ravaud, Philippe; Ekouevi, Didier K
Abstract : Objective: Patients living with HIV infection (PLWH) in sub-Saharan Africa face an important burden of treatment related to everything they do to take care of their health: doctor visits, tests, regular refills, travels, and so on. In this study, we involved PLWH in proposing ideas on how to decrease their burden of treatment and assessed to what extent these propositions could be implemented in care. Methods: Adult PLWH recruited in three HIV care centres in Côte d'Ivoire participated in qualitative interviews starting with ' What do you believe are the most important things to change in your care to improve your burden of treatment? ' Two independent investigators conducted a thematic analysis to identify and classify patients' propositions to decrease their burden of treatment. A group of experts involving patients, health professionals, hospital leaders and policymakers evaluated each patient proposition to assess its feasibility. Results: Between February and April 2017, 326 participants shared 748 ideas to decrease their burden of treatment. These ideas were grouped into 59 unique patient propositions to improve their personal care and the organisation of their hospital or clinic and/or the health system. Experts considered that 27 (46%), 19 (32%) and 13 (22%) of patients' propositions were easy, moderate and difficult, respectively, to implement. A total of 118 (36%) participants offered at least one proposition considered easily implementable by our experts. Conclusion: Asking PLWH in sub-Saharan Africa about how their care could be improved led to identifying meaningful propositions. According to experts, half of the ideas identified could be implemented easily at low cost for minimally disruptive HIV care.